Síntese de aluminato de zinco (ZnAl2O4) pelo método de complexação metal-quitosana e seu uso como fotocatalisador - Stringhini, Fabiane Marconato (2013)
In this work, the synthesis of the oxide zinc aluminate spinel (ZnAl2O4) was realized by the metal-chitosan complexation method in different calcinations temperatures with the purpose of studying their influence in the physical properties of the material. The powders obtained were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR), nitrogen adsorption-dessorption by the Brunauer-Emmett-Teller (BET) method, scanning electron microscopy (SEM) and differential thermal analysis (DTA). This material was used as catalyst and its activity was investigated in the photodegradation reaction of an organic textile dye under ultraviolet irradiation. In order to do this research, aqueous solutions of the dye were used in different initial concentrations and different amounts of catalyst. In the photocatalytic tests, parameters like the influence of the dye s calcinations temperature, the influence of the dye s initial concentration and the effect of the catalyst concentration. The rates constants of photocatalytic reactions were determined. The summary of the results demonstrated the obtainment of mesoporous particles with high surface area. The photocatalytic tests indicated that the material prepared in this work shows satisfactory photocatalytic activity for the degradation of the organic pollutant. The initial concentration of the dye as well as the catalyst mass had significant influence in the photocatalytic process.